Ревизия рода Hyptioxesta (Lepidoptera, Noctuidae) с описанием нового вида - Кононенко, В.С. (Вестник зоологии, 1984)
A Revision of the Genus Hyptioxesta (Lepidoptera, Noctuidae) with Description of
a New Species. Kononenko V. S.— Vestn. zool., 1984, No. 1 The genus Hyptioxesta is
transferred from subfamily Acontiinae to Noctiinac. H. hurenizool sp. n. is described
from Sikhote-Alin Mts. It differs from similar H. penthima Ersch. by paler wing colouration, diffused wing pattern, straight second band, absence of terminal stripe on hind
wing underside and by genitalic characters. Estimata magadanica Kononenko is
transferred to the genus Hyptioxesta.